(untitled) (Journal of the College of Basic Education, 2024)
The subject of Arabic calligraphy and Islamic ornamentation is one of the basic and important materials in the educational and educational process, which is related to the life of the student because it is a key factor in the development of the theoretical and skillful side, so the subject of Arabic calligraphy needs attention, especially through the use of modern teaching strategies that help students Concepts of Arabic calligraphy and decoration, and through the researcher teaching this subject in the College of Basic Education - Department of Art Education The researcher sought the existence of a weakness in the cognitive theoretical information, for which he conducted this scientific research through which he intends to find a solution to the problem. Research objective: To identify the impact of the active learning strategy on acquiring the concepts of Arabic calligraphy and decoration for students of the Department of Art Education. In order to achieve the goal of the research, the researcher used the experimental design in the experimental and control groups with a post-test for the concepts of Arabic calligraphy and ornamentation, on a sample of the students of the College of Basic Education, who numbered (84) distributed in two halls, one of which represented the experimental and the other represented the control. using the spss program. The most important search results showed: 1- The superiority of the experimental group that studied according to the strategy over the control group, and this indicates the impact of the strategy on acquiring concepts among the sample. 2- The adoption of teaching according to the strategy makes the teacher diversify the activities and methods of teaching in the educational situation. The search was recommended by Platy: 1- The need to use active learning strategies in teaching and not be limited to the traditional method. 2- The necessity of paying attention to the concepts of Arabic calligraphy and ornamentation, and linking them to the skill aspect, because they add activity and vitality to the lesson and motivate students to search for information. Suggestions: 1- Applying active learning strategies in developing the skill side of Arabic calligraphy and decoration. 2- The use of active learning strategies in other study materials and stages.